Differences in characteristics of Central Giant Cell Granuloma with Ameloblastoma, Odontogenic Myxoma and Aneurysmal Bone Cyst through radiographic approach - Mandiasa, Prestisia Peramiswara; Sarianoferni, Sarianoferni; Annariswati, Icha Artyas (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This study aims to determine the differences in the characteristics of Central Giant Cell Granuloma with Ameloblastoma, Odontogenic Myxoma, and Aneurysmal Bone Cyst through a radiographic approach so as to expand understanding of the characteristics of Central Giant Cell Granuloma with benign lesions of the oral cavity that have similar characteristics. Review: The data used in this study are research journals published on PubMed and Google Scholar search engines. Selecting keywords namely Radiology, Central Gaint Cell Granuloma, Differential Diagnosis by formulating research questions to provide an operational framework using the PICO framework (P: Patient, Population, or Problem; I: Intervention or Exposure; C: Comparison; Outcome). Data collection procedures were carried out through journal identification, then data reduction was carried out, namely selecting journals that were in accordance with the research concept, so that inclusion and exclusion criteria were determined and tested for eligibility and completeness of journals. Conclusion: In this literature review, it was found that Central Giant Cell Granuloma can be diagnosed in comparison with Ameloblastoma, Odontogenic Myxoma, and Aneurysmal Bone Cyst. A total of 41.6% compared with Ameloblastoma, so Ameloblastoma has a higher percentage. 19.4% compared with Odontogenic Myxoma and 38.8% compared with Aneurysmal Bone Cyst.